Anti-inflammatory Property of Gels Formulated using Dacryodes edulis Bark Ethanol Extract (African Journal of Biomedical Research, 2023)
This work was done to assess the anti-inflammatory property of gels formulated using ethanolic extract of Dacryodes edulis   bark. Dacryodes edulis   bark was ground to coarse powder and macerated in ethanol for 48 h. It was filtered by straining using muslin cloth. The filtrate was dried for 12 h in a water-bath at 73±1oC and the dried extract was stored in an airtight container. The extract was evaluated for its phytochemical composition. The extract was evaluated for anti-inflammatory activity and skin irritation study. The gels were made by incorporating the extract into a gel base made of either carbopol or sodium carboxymethylcellulose (NaCMC) as the gelling agent. The gels were evaluated for anti-inflammatory activity, spreadability, pH, viscosity and physical appearance. The Dacryodes edulis   bark ethanolic extract was found to contain flavonoids, tannins, reducing sugars, alkaloids, terpenoids, cardiac glycosides and saponins. The extract has good anti-inflammatory property. The gels formulations that contained propylene glycol as penetration enhancer showed higher anti-inflammatory activity than those without it. The gels prepared with carbopol as gelling agent exhibited higher anti-inflammatory activity than those formulated with NaCMC.  There was no skin irritation by any of the formulations. The gels had good homogeneity and consistency with no phase separation. The pH ranged from 4.1 to 8.5, while the spreadability ranged from 0.9 to 1.9 cm. The viscosity was between 12,250 to greater than 20,250 mPas. Gels that displayed anti-inflammatory activity with good physicochemical properties were produced using Dacryodes edulis   bark ethanolic extract.
Keywords: Dacryodes edulis; anti-inflammatory activity; gels; viscosity; spreadability